2017
DOI: 10.1007/978-1-4939-6927-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Rotation of the Flagellar Motor by Bead Assay

Abstract: The bacterial flagellar motor is a reversible rotary nano-machine powered by the ion flux across the cytoplasmic membrane. Each motor rotates a long helical filament that extends from the cell body at several hundreds revolutions per second. The output of the motor is characterized by its generated torque and rotational speed. The torque can be calculated as the rotational frictional drag coefficient multiplied by the angular velocity. Varieties of methods, including a bead assay, have been developed to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Most importantly, it is also has the largest surface area in motion, which potentially increases its susceptibility to surface based affects such as increased stickiness. To examine the mechanism of inhibition, and to rule out potentially confounding cell-surface effects that may have influenced earlier experiments using tethered cells, we used a 1 µm polystyrene bead assay (44) to examine the effects of BB2-50F and HM2-16F on rotation. We observed that phenamil in some instances slowed, but did not stop, rotation, whereas BB2-50F and HM2-16F stopped rotation and fixed the location of the bead (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it is also has the largest surface area in motion, which potentially increases its susceptibility to surface based affects such as increased stickiness. To examine the mechanism of inhibition, and to rule out potentially confounding cell-surface effects that may have influenced earlier experiments using tethered cells, we used a 1 µm polystyrene bead assay (44) to examine the effects of BB2-50F and HM2-16F on rotation. We observed that phenamil in some instances slowed, but did not stop, rotation, whereas BB2-50F and HM2-16F stopped rotation and fixed the location of the bead (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The tethered cell assay is an excellent approach for measuring variations in the response of individual cells to treatment and for initial compound screening, however it does not provide positional information for the rotor or assess performance at low load (41). To examine the mechanism of inhibition, and to rule out potentially confounding cell-surface effects that may have influenced earlier experiments using tethered cells, we used a 1 µm polystyrene bead assay (42) to examine the effects of BB2-50F and HM2-16F on rotation. We observed that phenamil in some instances slowed, but did not stop, rotation, whereas BB2-50F and HM2-16F periodically stopped rotation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it is also has the largest surface area in motion, which potentially increases its susceptibility to surface based affects such as increased stickiness. To examine the mechanism of inhibition, and to rule out potentially confounding cell-surface effects that may have influenced earlier experiments using tethered cells, we used a 1 μm polystyrene bead assay (44) to examine the effects of BB2-50F and HM2-16F on rotation. We observed that phenamil in some instances slowed, but did not stop, rotation, whereas BB2-50F and HM2-16F stopped rotation and fixed the location of the bead (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated in a sample chamber for 15 min to attach on the coverslips via their sticky filament. After flushing the unbound cells with the same buffer, spinning cells, which attach on the coverslips via single filaments, were captured at 60 fps by CMOS camera for 10 s [24]. To observe the effect of the electrochemical potential of Mg 2+ on the motor speed, the buffer in a sample chamber was exchanged by running the buffer containing appropriate concentrations of EDTA, MgCl 2 , or CCCP (carbonyl cyanide m-chlorophenyl hydrazone).…”
Section: Rotation Measurement By Tethered Cell Assaysmentioning
confidence: 99%